AB0731 Risk factors and prevalence of osteoporosis in patients with systemic lupus erythematosus. (23rd January 2014) - Rodríguez-García, V.; Romero-Barco, C.M.; Manrique-Arija, S.; Jimenez-Nuñez, F.G.; Panero, B.; Ordoñez, M.C.; Nieves-Martín, L.; Belmonte, M.A.; Coret, V.; Cano, L.; Irigoyen, M.V.; Rodríguez-Perez, M.; et al.
Abstract : Objectives: To determine the prevalence and risk factors of osteoporosis in patients with Systemic Lupus Erythematosus (SLE) in our hospital. Methods: Design: Retrospective study. 101 SLE-patients were studied in the Rheumatology Department in Carlos Haya Hospital in Malaga. Patients' disease and demographic data (including SLEDAI) were collected. Bone mineral density (BMD) was measured at the lumbar spine (LS) and femoral neck (FN) with a DEXA-LUNAR- PRODIGY. The results were classified according to WHO criteria. Thoracic and lumbar spine radiographies were assessed using the Genant method. Results: Data from 98 SLE-patients were available for analysis (94% women, mean age 42±14 years). Only 61 patients (62%) had a DEXA. Patients with DEXA were similar to others in terms of gender, race, history of fracture, alcohol, tobacco, sedentary, photosensitivity or use of corticosteroids. However, patients with DEXA were older (42.3±14 years vs. 40.6±13.5 years, T-test p=0.002), had a longer duration of lupus (120.7±103.3 months vs. 89.6±68.4, U of MW p no significant differences were found in the prolonged steroids taking (>6 months) [4 (44.4%) vs. 30 (66.7%), Fisher's exact test p=0.266] and SLICC (0.9±0.9 VS. 0.9±1.5, T-test p=0.937). Conclusions: The prevalence of osteopenia and osteoporosis in our SLE-patients is greater than in general population and it is more frequent in older age, menopausal status and history of fracture. The profile of patients with DEXA reflects that this test is not request systematically in clinical practice but only to those patients with more osteoporosis risk, this is a considerable bias in our study. The small sample size and the systematic use of prophylactic treatmentin patients treated with corticosteroids may be also explained why it was not found relationship between glucocorticoids and low mineral bone density Disclosure of Interest: None Declared